Integration von Flüchtlingen in den Arbeitsmarkt als Chance für Diversity Management: Einführung und ausgewählte Beispiele im Kreis Steinfurt - Charlene Schröder; Ulrike Weber (readbox unipress, 2017)
– The rising number of the refugees in Germany has many facets. In addition to the omnipresent public debate concerning the number of refugees who will be allowed to enter the country, there are many aspects affecting the job market such as the newly passed integration law. Also companies change their views on refugees. To stop the rising number of unemployed refugees and to intercept at the same time the dwindling of skilled workers, enterprises seize the employment and integration of refugees as a chance and consciously promote it. For enterprises to take a step forward and even benefit from a diverse workforce, authorities should remove administrative barriers, reservations among companies, their employees as well as refugees should be diminished, and integration should be designed deliberately. The present publication is based on a master's thesis and helps enterprises as a guide to draft an integration program administratively, organizationally and culturally successfully. The thesis examines exemplarily how integration of refugees was implemented in selected enterprises in the county of Steinfurt. Based on interviews with five local county authorities and twelve companies, the obstacles, enterprise-internal processes and activities which are connected with the integration of refugees in the work force have been identified. In addition, the publication illustrates how the employment of refugees and their integration can promote diversity management in enterprises.
Keywords: 330; Arbeitsmarktintegration; Flüchtlinge; Diversity Management; Deutschland; Arbeitsmarktintegration; Flüchtlinge; Diversity Management; Deutschland